A new native plant in the neighborhood: effects on plant–pollinator networks, pollination, and plant reproductive success. Issue 7 (30th April 2020) - Hernández‐Castellano, Carlos; Rodrigo, Anselm; Gómez, José María; Stefanescu, Constantí; Calleja, Juan Antonio; Reverté, Sara; Bosch, Jordi
Abstract: Ecological communities are dynamic entities subjected to extinction/colonization events. Because species are connected through complex interaction networks, the arrival of a new species is likely to affect various species across the community, as observed in plant biological invasions. However, plant invasions usually represent extreme scenarios in which the community is strongly dominated by the alien species, confounding the effects of a change in species composition with a massive increase in floral resource availability. Our study addresses changes in plant community composition involving native species, a common phenomenon under the current climate change scenario in which plants are modifying their distribution ranges. We experimentally manipulated patches of a natural scrubland community by introducing a native plant (henceforth colonizing plant). To avoid introducing a disproportionate amount of floral resources we adjusted the number of flowers of the colonizing plant to the amount of floral resources locally available in each patch. We had two objectives: (1) to analyse the effects of the arrival of a new plant on the pollinator community, the rearrangement of plant–pollinator interactions and the structure of the plant–pollinator network; (2) to evaluate potential consequences for pollination and the reproductive success of resident plant species. The colonizing plant acted as a magnet species, attracting bumble bees and facilitating interactions to other plants through spill‐over. The introduction of the colonizing plant also affected the structure of plant–pollinator networks (colonized networks were more generalized and more nested than control networks) and modified the arrangement of plant and pollinator species into modules. Ultimately, these changes resulted in higher heterospecific (but not conspecific) pollen deposition and had contrasting effects on the reproductive success of two resident plant species (higher fruit set and lower seed set, respectively). Our study shows that relationships between plants and pollinators are rapidly rearranged in response to novel situations (even when the new plant is not overly dominant), with important functional consequences on pollination and plant reproductive success. Our study establishes a link between network structure and pollination and plant reproductive success, which may be mediated by differences among pollinator species in foraging behavior.